COLTRIMS Imaging of Molecular Fragmentation Dynamics of CO Molecules Induced by Slow He2+ Ions - Feras R. Afaneh (Jordan Journal of Physics, 2025)
We study the multiple ionization and fragmentation of CO in collisions with slow He2+ ions. Correlated measurements of all fragment ions and the projectile final charge state were performed using our coincidence COLTRIMS imaging technique coupled to projectile charge state separation. Complete fragmentations of CO, following double electron capture, into Cm++On+ with a total charge of 4 were investigated. The kinetic energy release (KER) distributions and their dependence on the molecule-axis orientation and on the projectile ion velocity were studied. A strong dependence of the kinetic energy release on the velocity of the He ions is observed. Furthermore, we find that the KER values are shifted toward higher energies when the molecule is aligned with the beam direction. Keywords: Ion-molecule collisions; Molecular fragmentation; Kinetic energy release; Recoil-ion spectroscopy; Molecular orientation; Multi-hit COLTRIMS imaging. PACS: 34.70.+e, 34.80.Gs, 34.50.Gb.